2011
DOI: 10.4103/2230-973x.85962
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of aceclofenac in polyamidoamine dendrimer solutions

Abstract: In the present study we investigated the effect of polyamidoamine (PAMAM) dendrimers on the aqueous solubility of aceclofenac. The aqueous solubility of aceclofenac was measured in the presence of dendrimers in distilled water. The effect of variables, such as pH condition, concentration, temperature and generation (molecule size) of dendrimer, has been investigated. Results showed that the solubility of aceclofenac in the dendrimer solutions was proportional to dendrimer concentration. The order in which the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…This suggested that lauroyl chain should be functionalized to lower PAMAM generation (G0) rather than high PAMAM generations for optimal drug delivery and solubility of NAP. Similar observations were previously reported by Patel et al and Choudhary et al for solubility enhancement studies of various PAMAM dendrimer generations to aceclofenac ( 17 ), another poorly soluble NSAID drug [ 55 , 56 ].…”
Section: Experimental Insights On Pamam-drug Interactions For Enhasupporting
confidence: 88%
“…This suggested that lauroyl chain should be functionalized to lower PAMAM generation (G0) rather than high PAMAM generations for optimal drug delivery and solubility of NAP. Similar observations were previously reported by Patel et al and Choudhary et al for solubility enhancement studies of various PAMAM dendrimer generations to aceclofenac ( 17 ), another poorly soluble NSAID drug [ 55 , 56 ].…”
Section: Experimental Insights On Pamam-drug Interactions For Enhasupporting
confidence: 88%
“…It has been proved that dendrimers may have the potential to improve the solubility of low aqueous soluble drugs and as a carrier for bioactive materials. [ 3 ] Among them, the polyamidoamine (PAMAM) dendrimer is one of the well-known dendrimers and has been proven as a carrier to improve water solubility and the rate of dissolution of drugs such as ketoprofen,[ 4 ] ibuprofen,[ 5 ] aceclofenac,[ 6 ] and riboflavin. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…The effect of dendrimer hydrogen particle focus on the solvency improvement of aceclofenac can be a direct result of a power association among NH 2 groups of dendrimer and furthermore the COOH bunch of the medication. The aceclofenac dissolvability was observed to be correspondingly relative to the temperature of the dendrimer goals 35 .…”
Section: Fig 5: Factors Affecting Dendrimer-mediated Drug Solubilizamentioning
confidence: 98%
“…Aceclofenac is just about insoluble in water. Concentrates have reportable that the solvency of Aceclofenac has significantly expanded exploitation G0 PAMAM dendrimers 35 .…”
Section: Fig 5: Factors Affecting Dendrimer-mediated Drug Solubilizamentioning
confidence: 99%